Designing Performance Appraisal For Pplc - Rafael Wahyu Wicaksono; Aurik Gustomo (Jurnal Impresi Indonesia, 2025)
PPLC is a wholesaler company operating both in online and offline stores in the DKI Jakarta area, which mainly sells plastics products for both retailers and customers. PPLC was founded in 2022 and could be considered a new company. Although new, their revenue shows otherwise, as the demand for their plastics products peaked in the beginning of 2025. Currently PPLC faced a significant problem which resulted in the ratings of their store. Packaging employees constantly make mistakes in packaging the wrong products. From the root cause analysis (RCA) it was found that one of the root causes was the new implementation of performance appraisal. Furthermore, not all employees excluding packaging employees have proper performance appraisal methods. This research aims to improve the design of the performance appraisal, analyse the gap between the current performance appraisal with the ideal performance appraisal according to literature review to enhance the current performance evaluation. With the new design, it is hoped to improve the performances of the employees. This research uses a qualitative approach with semi-structured interviews as the primary data, which also combines secondary data such as organization’s data or documents. The interview data is analyzed using thematic analysis and to ensure quality of qualitative data, triangulation method is used in this research. The result of this research shows that there are several gaps such as the lack of job analysis, no documentation on the job descriptions for all positions, and no proper method of evaluation for all employees within the organization. The extensive improvements suggest a hybrid approach in evaluating employees; the use of both Management by Objectives and Graphical Rating Scale methods in the performance appraisal. Furthermore, job analysis is also conducted in this research to support the new proposed design of performance appraisal for all employees in PPLC.